The Effectiveness Of Culturally Responsive Teaching (CRT) As A Differentiated Learning Approach In Secondary Learning - Eka Siti Maullina; Budi Usodo; Laila Fitriana (Universitas Wiralodra, 2025)
This study aims to describe the effectiveness of Culturally Responsive Teaching (CRT) as a differentiated learning approach in mathematics. CRT is important to implement because it accommodates students' diverse cultural backgrounds, thus increasing learning participation and understanding. This study used a quantitative approach with a one-group pretest-posttest type pre-experiment design. The research subject was class VIII B of SMP Negeri 15 Surakarta, which was selected by simple random sampling from eight parallel classes. The treatment was conducted in three meetings. The research instruments included learning outcome tests, student activity observation sheets, and student response questionnaires. The results of descriptive analysis showed that the average score of learning outcomes increased from 57.73 to 85.30. The single-sample t-test showed this improvement was statistically significant at the 0.05 significance level. Student activities showed positive engagement of 88.66%, while negative engagement amounted to 6.70%. More than 70% of students responded positively to the CRT implementation. The results of this study show that the CRT approach is efficacious in improving learning outcomes, student engagement, and response, and is relevant to be applied in culturally diverse classrooms.